Inequity in cardiovascular care in the English National Health Service (NHS): a scoping review of the literature. (16th October 2016) - Asthana, Sheena; Moon, Graham; Gibson, Alex; Bailey, Trevor; Hewson, Paul; Dibben, Chris
Abstract: There is a general understanding that socioeconomically disadvantaged people are also disadvantaged with respect to their access to NHS care. Insofar as considerable NHS funding has been targeted at deprived areas, it is important to better understand whether and why socioeconomic variations in access and utilisation exist. Exploring this question with reference to cardiovascular care, our aims were to synthesise and evaluate evidence relating to access to and/or use of English NHS services around (i) different points on the care pathway (i.e. presentation, primary management and specialist management) and (ii) different dimensions of inequality (socioeconomic, age‐ and gender‐related, ethnic or geographical). Restricting our search period from 2004 to 2016, we were concerned to examine whether, compared to earlier research, there has been a change in the focus of research examining inequalities in cardiac care and whether the pro‐rich bias reported in the late 1990s and early 2000s still applies today. We conducted a scoping study drawing on Arksey & O'Malley's framework. A total of 174 studies were included in the review and appraised for methodological quality. Although, in the past decade, there has been a shift in research focus away from gender and age inequalities in access/use and towards socioeconomic status and ethnicity, evidence that deprived people are less likely to access and use cardiovascular care is very contradictory. Patterns of use appear to vary by ethnicity; South Asian populations enjoying higher access, black populations lower. By contrast, female gender and older age are consistently associated with inequity in cardiovascular care. The degree of geographical variation in access/use is also striking. Finally, evidence of inequality increases with stage on the care pathway, which may indicate that barriers to access arise from the way in which health professionals are adjudicating health needs rather than a failure to seek help in the first place.